ARTIFICIAL INTELLIGENCE AND LAW - Sayfullaev Sirojiddin (Web of Journals Publishing, 2025)
This article analyzes the impact of artificial intelligence (SI) technologies in the legal field, emerging legal problems and the possibilities of application of SI tools in law enforcement systems. Human rights, data security, accountability, and ethical criteria issues through SI-based systems were also addressed. The study aims to identify existing barriers to integration of SI and the legal sector and to promote promising solutions.
Keywords: Artificial intelligence, law, ethical issues, liability, algorithmic decisions, data security.